Data Collection in Fragile States Innovations from Africa and Beyond - Hoogeveen, Johannes; Pape, Utz (Springer Nature, 2020)
'This open access book addresses an urgent issue on which little organized information exists. It reflects experience in Africa but is highly relevant to other fragile states as well.' -Constantine Michalopoulos, John Hopkins University, USA and former Director of Economic Policy and Co-ordination at the World Bank Fragile countries face a triple data challenge. Up-to-date information is needed to deal with rapidly changing circumstances and to design adequate responses. Yet, fragile countries are among the most data deprived, while collecting new information in such circumstances is very challenging. This open access book presents innovations in data collection developed with decision makers in fragile countries in mind. Looking at innovations in Africa from mobile phone surveys monitoring the Ebola crisis, to tracking displaced people in Mali, this collection highlights the challenges in data collection researchers face and how they can be overcome.